Internship and audit expectation gap among undergraduate students in Universiti Utara Malaysia - Md Ali, Azham; Lee, Teck Heang; Mohamad, Rosli; Ojo, Marianne (Emerald Group Publishing, 2008)
The accounting profession has long faced the issue of an audit expectation gap: being the gap between the quality of the profession's performance,its objectives and results, and that which the society expects.Studies have been carried out worldwide to determine the effect of education in narrowing the audit expectation gap.Extending the knowledge acquired, this paper investigates whether intership program could reduce the audit expectation gap in Malaysia.Using a pre-post method, the research instrument adapted from Ferguson el al. (2000) is administered to the UUM's accounting students before and after completing an internship program.The results show a significant change in their perceptions after the internship program.However changes in perceptions may not warrant an internship program as a means of reducing the audit expectation gap as misperceptions abaut the duties of auditors for fraud prevention and detection are still found among respondents. Nevertheless, an internship can still be used to complement audit education as it is an ideal way to expose students to professional issues and enables them to have a better insight of the actual performance and duties of auditors.